Chapter Processo formativo e transizione al lavoro: percorsi nell'Alta Formazione - Boffo, Vanna (Studies on Adult Learning and Education, 2022)
Restructuring personal and vocational training by means of the harbinger of a not merely economistic idea of employability represents a fundamental and ineradicable task of educational research and pedagogical reflection. The most obvious effect of such a re-understanding of employability in its function as a pedagogical principle and catalyst of formation, because of its dimension of connaturality with the subjective educational trajectory, is that of reinterpreting transition processes not from a discontinuous perspective, but from a process perspective. Hence the need to think and rethink ordinal architectures and understand the training process according to a logic of continuity and chain in which each individual educational and didactic proposal converges and makes the principle of employability transparent in a generative and transformative way.